A practical method for prenatal diagnosis of anal atresia by second trimester ultrasound screening - A retrospective study - Hsuan Ko; Yu-Ching Chou; Ksenia Olisova; Tung-Yao Chang (Elsevier, 2023)
Objectives: The study aimed to demonstrate the performance of anal atresia ultrasound screening in the second trimester and to describe associated experiences in a primary care fetal medicine clinic. Materials and methods: We retrospectively analyzed the medical records of fetuses who underwent a second-trimester screening at the Taiji clinic between November 2019 and May 2022. Fisher's exact test was conducted to investigate potential risk factors. Results: There were 28 459 fetuses screened in our clinic during the study period; eventually, 6 cases were diagnosed with anal atresia after birth. The incidence of anal atresia in our sample was 2.11 in 10 000. Based on our findings, potential risk factors significantly associated with anal atresia included: multiple pregnancies (p-value = 0.0185) and in-vitro fertilization (p-value = 0.038). Half of the anal atresia cases were associated with abnormalities affecting other organ systems, most frequently the genitourinary system (66.7%) and cardiovascular system (66.7%), especially persistent left superior vena cava (2 cases). Conclusion: Anal atresia is a malformation that requires extensive care; the clinical management after the prenatal discovery of its signs should include testing for chromosomal abnormalities and close monitoring of the amniotic fluid volume. Therefore, prenatal ultrasound screening for anal atresia in the second trimester is critical, particularly in the cases of multiple and IVF pregnancies, and multiple abnormalities. The fetuses with ultrasound signs of anal atresia should be followed at a later gestational period and referred to a specialized institution for postnatal management planning and parental counseling.